Genomic and phenotypic characterization of Streptococcus mutans isolates suggests key gene clusters in regulating its interaction with Streptococcus gordonii - Liu, Shanshan; Sun, Yu; Liu, Yudong; Hu, Fuyong; Xu, Li; Zheng, Qingwei; Wang, Qinglong; Zeng, Guojin; Zhang, Kai (Frontiers in Microbiology, 2022)
Streptococcus mutans (S. mutans) is one of the primary pathogens responsible for dental caries. Streptococcus gordonii (S. gordonii) is one of the early colonizers of dental plaque, and can compete with S. mutans for growth. In the present analysis, we explored key target genes against S. gordonii in S. mutans using 80 S. mutans clinical isolates with varying capabilities against S. gordonii. A principal coordinate analysis revealed significant genetic diversity differences between antagonistic and non-antagonistic groups. Genomic comparisons revealed 33 and 61 genes that were respectively positively and negatively correlated with S. mutans against S. gordonii, with RNA-sequencing (RNA-seq) highlighting 11 and 43 genes that were respectively upregulated and downregulated in the antagonistic group. Through a combination of these results and antiSMASH analysis, we selected 16 genes for qRT-PCR validation in which the expression levels of SMU_137 (malate dehydrogenase, mleS), SMU_138 (malate permease, mleP), SMU_139 (oxalate decarboxylase, oxdC), and SMU_140 (glutathione reductase) were consistent with RNA-seq results. SMU_1315c-1317c (SMU_1315c transport-related gene) and SMU_1908c-1909c were respectively downregulated and upregulated in the antagonistic group. The expression patterns of adjacent genes were closely related, with correlation coefficient values greater than 0.9. These data reveal new targets (SMU_137-140, SMU_1315c-1317c, and SMU_1908c-1909c) for investigating the critical gene clusters against S. gordonii in S. mutans clinical isolates.